Violence against Women in Bangladesh (Delta Medical College Journal, 2017)
Background: Violence against women has many forms including physical aggression or threats, sexual abuse, emotional abuse, controlling or domineering, intimidation, stalking, passive/covert abuse, and economic deprivations. Alcohol consumption and mental illness can be co-morbid with abuse and present additional challenges when present alongside patterns of abuse.Objective: The objective of this study was to find out the status of victims of Violence against Women along with the causes and consequences of this heinous crime.Materials and method: A retrospective cross sectional study was done in Dhaka Medical College on the victims who underwent treatment at One Stop Crisis Centre (OCC) and burn unit. The victims were interviewed and the data received were later on analyzed by computer and organized in tables. Total cases of Violence against Women were 1143 during the study period. Due permission was taken from the authority.Results: Among the victims about 63% belonged to 16 to 30 years of age group. Most of the victims (56%) were from low socioeconomic conditions, 60% of them were housewife and most of the victims (71%) were married. Dowry cases and familial conflict (33% and 32% respectively) were the main background behind Violence against Women.Conclusion: At community level, improvement of economic status of women as well as women empowerment is essential. Mass awareness about Violence against Women through mass media is needed to be diffused.Delta Med Col J. Jan 2017 5(1): 25-29